STRUKTUR INTRINSIK NOVEL SATYANING ATI KARYA I KOMANG ALIT JULIARTHA - Putu Eddy Purnomo Arta; Ida Ayu Diah Larashanti; I Kadek Ruminten (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
This research is entitled the intrinsic structure of the novel Satyaning Ati by I Komang Alit Juliartha. The aim is to find out the structure that builds the novel Satyaning Ati by I Komang Alit Juliartha. This study uses a structural approach or an objective approach, which is an approach that sees literary works as they are, examines and understands the story content. The data in this study, using qualitative data, in the form of words, sentences, dialogue between characters in the novel Satyaning Ati by I Komang Alit Juliartha. Primary data in this study are from the 164 pages of Satyaning Ati by I Komang Alit Juliartha's novel. This novel was published by Pustaka Ekspresi, in Tabanan in september 2016. This study analyzes the intrinsic elements of a novel Satyaning Ati by I Komang Alit Juliartha so that readers can better understand the constructive structures that include: themes, characters and characterizations, settings, plot, mandate, and language style. The technique used by the writer is by reading and analyzing the entire content of the novel Satyaning Ati by I Komang Alit Juliartha so that the writer can determine the intrinsic elements that build the novel. Literary works are human creations that express the thoughts, ideas, understandings and responses of their creators about the nature of life by using imaginative and emotional language. The literary works are human creations that express the thoughts, ideas, understandings and responses of their creators about the nature of life by using imaginative and emotional language. The novel is literary works that reveal various aspects of people's lives. Novel Satyaning Ati by I Komang Alit Juliartha is a literary work built by various intrinsic elements that are coherent and cohesive. In the novel Satyaning Ati by I Komang Alit Juliartha, there is a message conveyed by the author through the behavior of the characters in the novel. Hopefully this research can be useful for writers and society. So the novel is not just a mere reading, but gives a moral message to the social life of the community.